The Implementation and Evaluation of a Media Literacy Intervention About PAES Use in Sport Science Students - Mallia, Luca; Chirico, Andrea; Zelli, Arnaldo; Galli, Federica; Palombi, Tommaso; Bortoli, Laura; Conti, Cristiana; Diotaiuti, Pierluigi; Robazza, Claudio; Schena, Federico; Vitali, Francesca; Zandonai, Thomas; et al. (Frontiers in Psychology, 2020)
With respect to both competitive and amatorial/fitness sports, media may strongly influence young people’s opinions and behaviors concerning the use of PAES (Performance and Appearance Enhancing Substances). The present investigation addressed this topic by focusing on sport sciences students’ beliefs concerning the possible role of media and on the implementation and evaluation of a PAES-focus media literacy intervention conducted with sport science students. This study relied on a sample of 521 students (attrition rate 10.3%) (45.1% female, mean age=22.6, SD=2.20), which provided baseline data on students’ levels of media literacy concerning the use of PAES (i.e., “descriptive sample”), and a sample of 248 students, which participated to and provided data on the media literacy intervention. This latter sample included a group of 128 students (44.5% female, mean age=23.03, SD=3.76) who actively participated to the intervention (i.e., “intervention group”), and a group of 120 students who did not (i.e., “control group”, 53.3% female, mean age=22.25, SD=2.47). All students filled out media literacy questionnaires targeting students’ awareness of media influence, their views about the realism of media contents, their sense of confidence in dealing with media messages, and their positive attitudes toward PAES use. Analyses of questionnaire data showed that students are relatively quite aware of media influence on people’s views and behaviors with respect to PAES use. At the same time, students also believed that young people do not consider media as “realistic sources” of information; nonetheless, they also did not consider themselves so capable of dealing effectively with media messages. With respect to the intervention, students overall appreciated and greatly welcomed the educational program on media literacy, and the analyses of intervention data across intervention and control groups showed that key media literacy variables changed over time, attesting the overall effectiveness of the intervention.